Pilot Project in Educational Service Marketing : Case Study: Poltekkes Kemenkes Kalimantan Timur - Ratna Wati; Sri Wahyuni; Desi Iska Fadhila; Andi Sirajuddin; Nur Laili; Masrur Yahya (Eastasouth Institute, 2026)
Digital transformation in educational service marketing has become a strategic necessity for enhancing institutional competitiveness, compelling educational institutions to adopt adaptive and innovative marketing strategies. This study aims to analyze the implementation of the Ministry of Health (Kementerian Kesehatan/Kemenkes) branding at Poltekkes Kemenkes East Kalimantan, one of five Poltekkes designated as pilot projects. The study focuses on the optimization of Instagram as a medium for educational service marketing. A qualitative case study approach was employed. Data were collected through in-depth interviews, observation, and documentation. The findings indicate that digital branding implementation significantly improved institutional visibility, reflected in the increase of Instagram followers from 9,000 to 19,200 within three months. Four important findings emerged: transformation of digital strategy, academic community involvement, effectiveness of value-based content, and the gap between awareness and engagement. The study concludes that digital branding effectiveness is determined not only by content distribution but also by audience interaction quality.